SmartNutri: An Android-Based Application to Improve Parental Nutrition Literacy and Growth Monitoring for Children Under Five Years Old - Kaharu, Nur Alinuddin; Wildan (Talenta Publisher, 2026)
Stunting and undernutrition among children under five remain major public health challenges in Indonesia, primarily due to low parental nutrition literacy, limited access to educational resources, and the absence of consistent household-level growth monitoring. These issues lead to poor nutritional practices and hinder national efforts to reduce stunting. Addressing these problems requires innovative, evidence-based digital interventions that can simplify complex nutrition information into practical guidance for parents. This study aims to develop and evaluate SmartNutri, an Android-based nutrition education application designed using Object-Oriented Programming (OOP) and the Waterfall development model. The application integrates a nutrition calculator, growth monitoring dashboard, and menu recommendations aligned with the Indonesian Ministry of Health Regulation No. 2 of 2020 and WHO growth standards, forming a comprehensive and user-friendly platform. A mixed-method approach was used, involving requirement analysis from 50 parents and 10 Posyandu health workers, iterative software development, and quantitative usability testing. The system achieved 100% functional accuracy across 25 test cases and an average System Usability Scale (SUS) score of 84.6 (“Excellent”), reflecting high user satisfaction and operational stability. Parental nutrition knowledge significantly increased from 58.4 ± 10.2 to 81.7 ± 8.9 (p < 0.001) after four weeks of use, confirming SmartNutri’s educational effectiveness. SmartNutri successfully bridges the gap between nutrition literacy and behavioral practice, providing a scalable, evidence-based digital tool to support early childhood nutrition. Future research will focus on long-term impact assessment, integration with community health systems, and AI-driven personalization to enhance engagement, scalability, and public health relevance.